2019
DOI: 10.1371/journal.pone.0209841
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of early vascular reactions in biodegradable and durable polymer-based drug-eluting stents in the porcine coronary artery

Abstract: Current drug-eluting stents have abluminal polymer coating; however, thrombus formation in these compared with that in uniformly coated stents remains controversial. We evaluated thrombus formation and early endothelialization after using abluminal biodegradable polymer-coated sirolimus- (BP-SES), and everolimus-eluting stents (BP-EES) versus a durable polymer-coated everolimus-eluting stent (DP-EES) in an in vivo setting. BP-SES, BP-EES, and DP-EES (n = 6 each) were implanted in coronary arteries of 12 mini-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, experimental data that validated the neointima after dual-polymer (DP)-EES and BP-SES implantation revealed that the number of cell tight junctions in the neointima after BP-SES implantation was significantly higher than that after DP-EES implantation. As a result, the authors concluded that the stability and robustness of the neointima was higher after BP-SES implantation [12]. The risk of a hypersensitive reaction caused by the remaining polymer is recognized as a major problem [2,4,5].…”
Section: Pathological Healing Process and Qualitative Evaluation Of Healing After Bp-sesmentioning
confidence: 99%
“…Moreover, experimental data that validated the neointima after dual-polymer (DP)-EES and BP-SES implantation revealed that the number of cell tight junctions in the neointima after BP-SES implantation was significantly higher than that after DP-EES implantation. As a result, the authors concluded that the stability and robustness of the neointima was higher after BP-SES implantation [12]. The risk of a hypersensitive reaction caused by the remaining polymer is recognized as a major problem [2,4,5].…”
Section: Pathological Healing Process and Qualitative Evaluation Of Healing After Bp-sesmentioning
confidence: 99%
“…In recently conducted studies Ultimaster has demonstrated good overall device performance, in the ACS cohort [ 19 ]. These favorable ACS-related outcomes might be linked to the presence of biodegradable polymer, which intensifies the alleviation of vascular inflammation and accelerates endothelial maturation, which is crucial in these high-risk patients [ 20 ]. Considering that in our study the rates of 1-year composite endpoints-TLR in the Ultimaster arm were lower than previously described [ 21 ] (5.4% vs 7.9%), we might assume that the Magmaris might demonstrate the outcomes compared to the ones observed in the new-generation DES devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, DP-DES may induce stent thrombosis through local hypersensitivity reactions and inflammation caused by polymer persistence [ 4 , 5 ]. To overcome this limitation, new-generation DES, including biodegradable polymer DES (BP-DES) and polymer-free DES, have been developed [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%